PREDIKTIVNA VRIJEDNOST BAZIČNIH MOTORIČKIH SPOSOBNOSTI NA REZULTATE SITUACIONO-MOTORIČKIH SPOSOBNOSTI FUDBALERA UZRASTA 14 - 16 GODINA - Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Basic goal in soccer game is to defeat rival with as much as possible scored goals. Beside this goal much more smaller tasks in defense and attack have to be resolved, what helps to resolving the main goal. Game needs adjustment to movement of player in specific occasion. Leading of ball is significant capacity which is related with faze of game- attack. Mentioned capacity is made of running speed in different direction, changing direction and controlling the ball. Capacity of controlling the ball, limits or accelerates maximum speed of leading the ball. Main goal of this research is to find predictive value of basic motor abilities on criteria (results in situation-motor tests of leading the ball). Research has been conducted on representative sample of 147 soccer players age 14- 16, and they are all members of clubs from first and second division in Serbia and Montenegro and they are all from territory of Montenegro. Predictive variables in this research are 25 motor tests. Criteria variables are results in situation-motor tests and they are: SNBV- 20 m of leading the ball, and SNBVPO- leading the ball in semicircle. Results of regressive analyze have shown that prediction of results about speed of leading the ball is possible, and based on motor tests whose intentional objects of measuring are explosive strength and coordination